Kerentanan Kemiskinan di Sulawesi Selatan: Analisis Vulnerability As Expected Poverty dan Klaster Spasial - Triany, Nur Hilda (Jurnal Ekonomi Kependudukan dan Keluarga, 2026)
This study aims to analyze the determinants of poverty vulnerability in South Sulawesi by integrating spatial dimensions into risk estimation models. Using micro-data from the March 2024 National Socio-Economic Survey (Susenas) with individuals as the unit of analysis, this study applies the Vulnerability as Expected Poverty (VEP) and Local Indicator of Spatial Association (LISA) methods, estimated through an integrated logistic regression model. Empirical results indicate that while the average vulnerability is relatively low, risk distribution is highly concentrated in specific regional clusters. Key findings reveal that health insurance ownership and household assets are the dominant protective factors that drastically reduce vulnerability risk, outweighing the influence of employment status. Contrary to common assumptions, female individuals demonstrate better resilience compared to males. Spatially, residing in poverty clusters (hotspots) proves to be an independent determinant that strictly increases risk, confirming the existence of spatial poverty traps. This study recommends a policy reorientation towards strengthening universal health protection and implementing place-based policies in vulnerability pockets.